KEPUASAN DAN STRES KERJA SEBAGAI DETERMINAN TURNOVER INTENTION - Dyah Supriatin; Rofik Priyanto (Perwira Journal of Economics & Business, 2026)
Employee turnover intention has become a critical issue for organizations, as it directly impacts productivity, stability, and long-term business performance. This study aims to examine the influence of job satisfaction and work stress on turnover intention among employees of PT Tiga Putra Abadi Perkasa. Using a quantitative approach with a questionnaire-based survey, data were collected from 76 employees. The analysis employed descriptive statistics and multiple linear regression to test the proposed hypotheses. The findings reveal that job satisfaction has a significant negative effect on turnover intention, indicating that higher job satisfaction tends to reduce employees’ quitting the organization. Conversely, work stress shows a significant positive effect on turnover intention, suggesting that increased stress levels elevate employees’ likelihood of quitting. Simultaneously, both job satisfaction and work stress significantly influence turnover intention. These results highlight the importance of maintaining employee satisfaction and managing work-related stress to minimize turnover intention. The study provides practical implications for human resource management strategies aimed at enhancing employee retention and organizational commitment at PT Tiga Putra Abadi Perkasa Purbalingga.